Mitigating flow assurance challenges in deepwater fields using active heating methods - Myo,Thant MM; Mohd,Sallehud-Din MT; Hewitt,GF; Hale,CP; Quarini,GL (SPE Middle East Oil and Gas Show and Conference Meos Proceedings, 2011)
Flow assurance challenges, mainly of hydrates and wax depositions, are amongst the key issues that must be resolved and mitigated to ensure that hydrocarbons can be efficiently and economically transported from well to processing facilities. As wells step further away from shore into deeper water, the flow assurance challenges are increasing tremendously due to prevalence of higher pressure and lower temperature conditions. Thus, the development of cutting edge technologies to cater for the ever increasing demand in exploring the hostile and technologically challenging deepwater fields is a matter of great urgency. One of the effective solutions to prevent the formation of wax or hydrates is to use active heating methods. This paper describes an overview of the available active heating methods and mechanisms which are being implemented as thermal management systems for flowline in deepwater fields. It also discusses the thermal performance calculation models available to aid the design and modelling of such systems. Some comparative studies are carried out to determine the advantages and disadvantages of each of the methods to establish a general reference source on the technology that provides the most significant economic impact without compromising the reliability and efficiency of the overall system. Active heating systems have been used in several projects in the North Sea, Gulf of Mexico and Offshore West Africa. This paper also summarizes these projects and their operating experience from open literature. In general, due to their operational flexibility and high efficiency through control of the pipeline temperature above the hydrate formation and wax deposition temperatures, active heating seems to be the most practical, economical and viable solutions in managing flow assurance issues; especially for the development of deepwater fields. Copyright 2011, Society of Petroleum Engineers.